ANALISIS PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA,DAN KOMPENSASI TERHADAP KINERJA GURU (Studi Kasus di SMA PPMI ASSALAM Surakarta) - Yahya, Muhammad; Rahman Hakim, Arif (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aims of the research are to analyze tha influeced between leadership style towardsteachers’performence, the influenced of job’motivation towards teachers’performance;also the influenced between leadership style, job’motivation, and compensation towardsteachers’performance of SMA PPMI ASSALAM Surakarta. The kinds of research isdescriptive quantitative research with population: 55 teachers. Data collection method is questionairethat has been tested the validity and reliability. Then the collected data were analyzed by usingdoubled linier regression technique, Test t, F, and R2 were caunted its relative and efectivecontribution. The research result showed that: 1. Leadership style has positive influenced towardsteachers performance of SMA PPMI ASSALAM Surakarta with efective contribution is 18,8%; 2.Job’motivation has positive influenced towards teachers’performance of SMA PPMI ASSALAMSurakarta with efective contribution is 24%; 3. Compensation has positive influenced towardsteachers’performance of SMA PPMI ASSALAM Surakarta with efective contribution is 15,1%. Itmeant that Motivation has positive influenced towards teachers’performance higher compared withothers variables.